Reconstructive Democratic Theory - Dryzek, John S.; Berejikian, Jeffrey (The American political science review, 1993)
While the idea of democracy has never been more universal or more popular, both democratic theory and the empirical study of democratic possibilities are in some disarray. We seek a productive reconnection of these two endeavors with democratic discourse through close attention to the language of democracy as used by ordinary people and political actors. Reconstructive inquiry determines how the individuals who are the potential constituents of any democratic order themselves conceptualize democracy and their own political roles and competences. We deploy an intensive method—Q methodology—for the study of individual characteristics, capabilities, and dispositions in combination with political discourse analysis. Four discourses are discovered in an analysis of selected U.S. subjects: contented republicanism, deferential conservatism, disaffected populism, and private liberalism. These results can be used to relate democratic theory to live possibilities in democratic discourse.